Potential of Maritime Transport for Ocean Liming and Atmospheric CO2 Removal - Caserini, Stefano; Pagano, Dario; Campo, Francesco; Abbà, Antonella; De Marco, Serena; Righi, Davide; Renforth, Phil; Grosso, Mario (Frontiers in Climate, 2021)
Proposals to increase ocean alkalinity may make an important contribution to meeting climate change net emission targets, while also helping to ameliorate the effects of ocean acidification. However, the practical feasibility of spreading large amounts of alkaline materials in the seawater is poorly understood. In this study, the potential of discharging calcium hydroxide (slaked lime, SL) using existing maritime transport is evaluated, at the global scale and for the Mediterranean Sea. The potential discharge of SL from existing vessels depends on many factors, mainly their number and load capacity, the distance travelled along the route, the frequency of reloading, and the discharge rate. The latter may be constrained by the localized pH increase in the wake of the ship, which could be detrimental for marine ecosystems. Based on maritime traffic data from the International Maritime Organization for bulk carriers and container ships, and assuming low discharge rates and 15% of the deadweight capacity dedicated for SL transport, the maximum SL potential discharge from all active vessels worldwide is estimated to be between 1.7 Gt/year and 4.0 Gt/year. For the Mediterranean Sea, based on detailed maritime traffic data, a potential discharge of about 186 Mt/year is estimated. The discharge using a fleet of 1000 new dedicated ships has also been discussed, with a potential distribution of 1.3 Gt/year. Using average literature values of CO2 of carbon dioxide removal per unit of SL added to the sea, the global potential of CO2 removal from SL discharge by existing or new ships is estimated at several Gt/year, depending on the discharge rate. Since the potential impacts of SL discharge on the marine environment in the ships' wake limits the rate at which SL can be applied, an overview of methodologies for the assessment of SL concentration in the wake of the ships is presented. A first assessment performed with a three-dimensional non-reactive and a one-dimensional reactive fluid dynamic model simulating the shrinking of particle radii, shows that low discharge rates of a SL slurry lead to pH variations of about 1 unit for a duration of just a few minutes.